2006
DOI: 10.1007/s00421-006-0187-8
|View full text |Cite
|
Sign up to set email alerts
|

Human muscle fatigue and elastic compressive stockings

Abstract: The present study was performed to test if elastic compressive stockings (ECSs) increase muscle fatigability during sustained muscle contraction or if it improves the recovery after fatigue. Surface electromyograms (EMGs) were recorded on 4 leg and thigh muscles, and static ankle dorsal flexion force levels were measured in the right limb of 15 healthy subjects. The subjects maintained a 50% maximum ankle dorsal flexion force (MVF) for as long as possible without and, after a 30 min rest, with a European class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…Although many studies have demonstrated the benefits of compression garments, the underlying mechanisms are still largely unconfirmed. Furthermore, results from a number of studies do not support some of the positive effects claimed by apparel manufacturers (Maton et al, 2006a;Sperlich et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Although many studies have demonstrated the benefits of compression garments, the underlying mechanisms are still largely unconfirmed. Furthermore, results from a number of studies do not support some of the positive effects claimed by apparel manufacturers (Maton et al, 2006a;Sperlich et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…In theory, the mechanism of action of EC garments is straightforward; the pressure exerted by EC garments increases the intramuscular pressure, consequently the cross-section of the veins is decreased and the blood flow is accelerated (Ibegbuna et al, 2003;Maton et al, 2006). Therefore, it has been speculated that EC garments can reduce venous stasis at rest and facilitate the venous return to the heart during exercise by increasing the efficacy of the muscle pump (Alimi et al, 1994;Raju et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, some publications demonstrate the benefits of compression, but other studies do not support the positive effects claimed by manufacturers of compression apparel [7,8].…”
Section: Wang Et Al / Reduce Muscle Activity Associate With Leg Cmentioning
confidence: 96%
“…However, the mechanism by which compressive garments enhance performance via the influences on the function and activity of neuromuscular system remains to be elucidated. Moreover, a considerable amount of studies failed to observe similar positive effects of compression garments probably because of the different locomotor movements that were tested in different experiments and the different materials and compressive levels of compression garments [7,18]. Therefore, further investigations are still warranted.…”
Section: Wang Et Al / Reduce Muscle Activity Associate With Leg Cmentioning
confidence: 99%